Stakeholder perceptions of the Considerate Constructors Scheme in UK construction. Issue 1 (5th August 2020) - Watts, Greg; Higham, Anthony; Alotaibi, Ali
Abstract : The Considerate Constructors Scheme (CCS) was introduced in 1997 to improve the image of the UK construction industry and has grown dramatically, with over 6000 construction and infrastructure projects registered valued at £43 billion. While evidence exists that the industry's image is improving, there is little research into the CCS perceptions of those tasked with scheme delivery. It is not clear if contractors engage with CCS willingly as proactive participants or succumb to the requirements of clients to win work simply. The aim of this paper is to gain an insight into contractor perceptions of CCS to aid clients and contractors ultimately in their delivery of the scheme and ensure that the CCS delivers the maximum benefit for stakeholders. A case study of a single infrastructure project registered with the CCS is utilised. All CCS documents were critically analysed, and interviews were conducted with clients, the contractor and residents. The findings contribute to an unexplored area of research and reveal the motivations behind why a contractor engages with the CCS, the advantages and drawbacks in the scheme's current enactment and key lessons on how the CCS could be administered and delivered more effectively for the benefit of all stakeholders.